ANALISIS PROFITABILITAS PENGEMBANGAN USAHA TERNAK ITIK DI KECAMATAN PAGERBARANG KABUPATEN TEGAL - Budiraharjo, K (MEDIAGRO, 2009)
The goals this research were knowed profit of duck effort and profitability of duck effort in Pagerbarang District at Tegal Regency. This research used survey method. The location of research in 3 sub district with random and responden is taken with census method. The result showed that every farmer maintained 231 ducks. Average profit in every month was Rp  1.744,384,78.   Every duck that maintained  to can to produce profit in every month  as Rp 7.551,45. This effort was profitable, showed value of  Gross Profit Margin  49.6%,  Return on Investment 226.3% and ratio of benefit and cost 100.8%. Keywords: Profit, Profitability